Using microprojectiles to study the ballistic limit of polymer thin films. Issue 16 (14th April 2020) - Chen, Shawn H.; Souna, Amanda J.; Soles, Christopher L.; Stranick, Stephan J.; Chan, Edwin P.
Abstract : In this work, a microballistic impact test called laser induced projectile impact test (LIPIT) was used to study the perforation behavior of polycarbonate thin films to demonstrate the importance of film thickness on the film's ballistic limit. Abstract : The dynamic impact between a particle and a planar material is important in many high impact events, and there is a growing need to characterize the mechanical properties of light-weight polymeric materials at dynamic loading conditions. Here, a laser-induced projectile impact test (LIPIT) is employed to investigate the ballistic limit ( V 0 ) and materials properties at impact velocities ranging from 40 m s −1 to 70 m s −1 . An analytical expression describing the various energy dissipation mechanisms is established to estimate the yield stress and elasticity for polycarbonate thin films. This measurement approach demonstrates the utility of using low sample mass for discovery of materials for impact mitigation, as well as high-throughput mechanical characterization at dynamic loading rates.